Avaliação de risco à saúde humana decorrente do uso de agrotóxicos em municípios do noroeste do Rio Grande do Sul - Schüller, Tariana Lissak (2023)
It is estimated that at least two thirds of all known pesticides are used in agriculture, bringing benefits to rural producers such as increased productivity, quality and reduction of pests. However, despite having important functions in agricultural production, their intense use can affect soil and water quality, causing ecological and human health risks, especially in the rural production environment. With this concern, the present study aims to evaluate the risk to human health of rural workers caused by the use of pesticides in 25 municipalities in the Northwest of Rio Grande do Sul. The evaluation was carried out using the methodology of “Assessment of risks to human health for the purpose of managing contaminated areas”, indicated by ABNT NBR 16.209. The Chemical Substances of Interest (SQI) used were glyphosate, paraquat dichloride, atrazine, mancozeb, 2,4-D and acephate. Surface soil was considered as the physical means of rural exposure and the exposure routes analyzed were dermal contact, ingestion and inhalation. Two exposure scenarios were considered, one with a single application of SQI to the soil and the other with repeated applications. Of the six pesticides mentioned, only atrazine is considered carcinogenic, as it has a carcinogenicity factor (SF) allowing the calculation of the carcinogenic risk. The other substances are classified as non-carcinogenic, having a reference dose (RfD). As it is the only carcinogen, atrazine can be considered the most toxic SQI among those analyzed. However, no carcinogenic risk was found by dermal contact or ingestion in either of the two scenarios related to the application of atrazine. Also, no noncarcinogenic risk was found by dermal contact or ingestion in any of the scenarios. Regarding the exposure route of soil particle inhalation, a carcinogenic risk was found for atrazine in all municipalities in the two analyzed scenarios. In the single application of non-carcinogenic substances, a health risk related to paraquat dichloride was found in all municipalities, except Cristal do Sul. Acephate poses a risk in case of inhalation of soil particles, in the single application scenario, in 72% of the municipalities. Considering non-carcinogenic substances and the multiple application scenario, a risk of inhalation by the SQI of paraquat dichloride was found in 16% of the municipalities. A non-carcinogenic risk was also found in the case of inhalation of particles with acephate, in the scenario of multiple application, in 44% of the municipalities. Considering the total risk, the municipality of Tiradentes do Sul had the highest total non-carcinogenic risk in the first exposure scenario and Novo Tiradentes in the second scenario. Vista Gaúcha had the highest total carcinogenic risk. Comparing the results obtained in the two scenarios of exposure to chemical substances evaluated in this study, the second scenario presents the lowest risk of damage to human health, and all municipalities have noncarcinogenic and carcinogenic risk for human health.